ENHANCING DESCRIPTIVE PARAGRAPH WRITING OF SECONDARY STUDENTS THROUGH SHARED WRITING - Mutiara Ayu; Zuraida Zuraida (Journal of Research on Language Education, 2020)
The objective of the study is to find out whether or not there was a significant difference in descriptive paragraph writing enhancement of secondary students who were taught through shared writing and those who were not. This study was conducted by using an experimental method. The sample of the study was 35 eighth grade students taken by using convenience sampling technique, 18 students belonged to experimental group and 17 students belonged to control group. The data were collected through pretest and posttest. In order to maintain validity, content validity was applied. Then, two raters were used to maintain reliability of the result. The experimental group was taught for twelve meetings by using Shared Writing. The result showed the students in the experimental getting the mean 14.67 with standard deviation 2.058 and control group getting the mean 12.00 with standard deviation 1.414 got a significant improvement in the posttest. There was a better significant improvement in descriptive paragraph writing in the experimental group who are taught by using Shared Writing if compared to the students in the control group.